2017
DOI: 10.3389/fendo.2017.00144
|View full text |Cite
|
Sign up to set email alerts
|

History of Gestational Diabetes Mellitus in Relation to Cardiovascular Disease and Cardiovascular Risk Factors in US Women

Abstract: BackgroundFindings from previous studies examining the association between gestational diabetes mellitus (GDM) and subsequent risk of cardiovascular disease (CVD) have been inconsistent and inconclusive. We aimed to examine the associations of a previous history of GDM with risk of CVD and status of cardiovascular risk factors in a nationwide population-based study in the United States.MethodsThis study included 8,127 parous women aged 20 years or older in the 2007–2014 cycles of the National Health and Nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 37 publications
2
46
2
4
Order By: Relevance
“…all the studies in this meta-analysis were published within the past 6 years); (2) the range of risk estimates that these studies have provided; and (3) uncertainty over whether the cardiovascular risk is entirely dependent upon type 2 diabetes. An earlier meta-analysis [23] included fewer studies and its risk estimate was compromised by the inclusion of two studies from our group that had overlapping participant populations [4,9] and studies with self-reported outcomes [7,24], as well as no assessment of the role of type 2 diabetes. The current meta-analysis was thus designed to address these gaps.…”
Section: Studymentioning
confidence: 99%
“…all the studies in this meta-analysis were published within the past 6 years); (2) the range of risk estimates that these studies have provided; and (3) uncertainty over whether the cardiovascular risk is entirely dependent upon type 2 diabetes. An earlier meta-analysis [23] included fewer studies and its risk estimate was compromised by the inclusion of two studies from our group that had overlapping participant populations [4,9] and studies with self-reported outcomes [7,24], as well as no assessment of the role of type 2 diabetes. The current meta-analysis was thus designed to address these gaps.…”
Section: Studymentioning
confidence: 99%
“…While it has been suggested14 that women with GDM history are characterized by higher prevalence of dyslipidemia compared with their normoglycemic peers, analysis of parous women from the 2007 to 2014 cycles of the National Health and Nutrition Examination Survey indicated that history of GDM is not significantly related with increasing levels of LDL-C 15. Thus, the aims of the current historical cohort study were to assess the course of lipid levels over time in postpartum women according to gestational diabetes status, taking into account potential confounders, such as comorbid conditions and body weight.…”
Section: Introductionmentioning
confidence: 97%
“…In different populations and geographical regions, the risk of developing T2D is 7.4 higher among women with GDM in comparison with women without GDM, both postpartum and later in life (6)(7)(8). In addition, young women with GDM are at greater risk of developing cardiovascular diseases (CVD) and coronary artery diseases (CAD), much attributable to the development of T2D (9,10). Moreover, there is reportedly increased risk of preeclampsia, asymptomatic bacteriuria, pyelonephritis and cesarean delivery among women with GDM (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is reportedly increased risk of preeclampsia, asymptomatic bacteriuria, pyelonephritis and cesarean delivery among women with GDM (11,12). Besides the adverse effects of GDM on the mother both in the short and long-terms, GDM was linked with many fetal and neonatal complications including macrosomia (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), shoulder dystocia (17), neonatal hypoglycemia (18) and congenital malformation (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%